EMBR-15. DIAGNOSTIC RE-EVALUATION AND POOLED CLINICAL DATA ANALYSIS OF PATIENTS WITH PREVIOUS DIAGNOSIS OF CNS-PNET. Issue 2 (22nd June 2018) - von Hoff, Katja; Haberler, Christine; Robinson, Giles; Sumerauer, David; Cho, Jaeho; Mynarek, Martin; Hwang, Eugene; Jacobs, Sandra; de Rojas, Theresa; Perek, Martha; Dufour, Christelle; Snuderl, Matija; et al.
Abstract: CNS-PNET is no longer regarded a single disease but encompassed many distinct molecular entities. After removal of the term from the 2016 WHO classification of CNS tumours, diagnostic and therapeutic uncertainty remains. Through a world-wide collaboration, tumour samples from patients with the "historic" diagnosis of CNS-PNET were re-evaluated by DNA methylation profiling (n=405) and blinded neuropathological panel review (n=256). Clinical data on treatment and outcome were pooled with data on previously published patients. The given numbers represent preliminary data of the ongoing project. The re-evaluation by DNA methylation identified many distinct entities as expected, including high grade glioma (HGG, n=70), embryonal tumors with multilayered rosettes (ETMR, n=57) and CNS-neuroblastoma with FOXR2 alteration (CNS-NB-FOXR2, n=42) as the most frequent molecular diagnostic categories. Poor clinical outcome was confirmed for patients with HGG (5y-PFS 12%/5y-OS 12%, n=24), and ETMR (5y-PFS 12%/5y-OS 18%, n=62), while most patients with CNS-NB-FOXR2 survived (5y-PFS 52%/5y-OS 96%, n=31). Seven of 12 relapses/progressions of CNS-NB-FOXR2 occurred in radiotherapy-naïve patients. Classification into other newly described and less common entities included HGNET-MN1 (n=19), HGNET-BCOR (n=11), and EFT-CIC (n=13). Independent neuropathological review demonstrated that samples of these entities presented as non-embryonal tumours. Furthermore, marked clinical differences exist (HGNET-MN1: 5y-PFS 25%/5y-OS 95%, n=22; HGNET-BCOR: 5y-PFS 0%/5y-OS 44%, n=16; CNS-EFT-CIC: 5y-PFS 40%/5y-OS 60%, n=10). Our results show that implementation of DNA methylation profiling together with histopathological analysis will improve prospective diagnostic accuracy and facilitates the retrospective outcome analysis of treatment protocols used for this variety of biologically distinct entities.